Do Accounting Standards Explain Differences in Earnings-price Ratios of Japanese and U.S. Firms? - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
This study exanunes the variation in earnings-price ratios across Japanese and US firms. Previous literature documents that Japanese firms have consistently lower earnings-price ratios than US. firms. The differences in earnings-price ratios have been primarily attributed to differences in Japanese and tl.S accounting standards However, Aron (1491)and French and Poterha (1991) provided a conflicting evidence on the argument of accounting standards that are the only cause of the differences in earnings price ratios The abiective of this study is to el-amine the issue that Japanese firms lower earnings price ratios is attributable to the differences in the accounting standards.. The results show that adjusting Japanese earnings does not entirely eliminate the differences in the earnings-price ratios between Japanese and U.S firms. On the average. the accounting standard differences account for 52 percent of the differences in the average earnings price ratios of Japanese and S. firms Controlling for differences in accounting standards dues ma eliminate the differences in the earnings-price ratios of the Japanese and US. firms. It is appropriate to conclude that although differences in accounting standards occur between Japanese and U.S. firms, rt is not the only factor that contributes to the differences in the earnings-price ratios of Japanese and U. firms